Concept Connectivity: An Educational and Research Framework for Scientific Learning in Optics, Photonics, and Electronic Education - Dingel, Benjamin (Archīum Ateneo, 2023)
We present a novel framework referred to as Concept Connectivity that aids in educating and engaging students by presenting the topic of the Special Theory of Relativity (STR) in a coherent and unified manner. It uses different analogue implementations of the STR coming from seemingly distinct fields of study such as (i) Optics, (ii) Photonics, and (iii) Electronics to connect not only to the concepts of the STR but to the various concepts from these different fields. In these analogue implementations, the fundamental characteristics of the different STR phenomena can be mimicked in many different ways. Concept Connectivity has two major benefits. First, from an educational perspective, undergraduate students can (i) understand advanced physical phenomena (like STR) from different points of view, (ii) bridge together different learnings or concepts from Physics, Optics, Photonics, and Electronics, and (iii) learn hands-on knowledge and engineering skills from Optics and Electronic experimentations when these analogues are incorporated in undergraduate physics lectures and laboratory courses. In this way, Concept Connectivity contributes to the growing pedagogical approaches used in science education with an emphasis on Photonics, Optics and Electronics. Second, from a research perspective, Concept Connectivity provides undergraduate students with a rare "taste of research experience"related to the challenge of merging different concepts in STR using principles in Optics, Photonics, and Electronics.